CORONARY REPERFUSION IN ST ELEVATION MYOCARDIAL INFARCTION: PROBLEMS AND SOLUTIONS - V. A. Markov; E. V. Vyshlov; R. S. Karpov (Российский кардиологический журнал, 2015)
The article analyzes a comparative efficacy of pharmacoinvasive reperfusion and primary percutaneous intervention in patients with ST elevation acute myocardial infarction in real clinical practice with fulfillment of Guidelines for the “first-medical-contact — balloon time”. The problem of choice is underlined on the most effective reperfusion method by emergency teams. The data is provided on a novel medication — non-immunogenic staphylokinase made in Russia (Fortelyzin®). The detailed analysis has been done on hospital mortality in myocardial infarction in Russian and abroad hospitals.